A study on marriage- related English and Vietnamese proverbs (From linguistic- cultural perspective) = Nghiên cứu về tục ngữ liên quan đến mối quan hệ hôn nhân trong tiếng Anh và tiếng Việt. M.A Thesis Linguistics: 60 22 15 - Trịnh, Thị Hương Giang (University of Languages and International Studies, 2017)
53 p. + CD-ROM + tóm tắt